Why do people use exotic plants in their local medical systems? A systematic review based on Brazilian local communities. - Patrícia Muniz de Medeiros; Washington Soares Ferreira Júnior; Marcelo Alves Ramos; Taline Cristina da Silva; Ana Haydée Ladio; Ulysses Paulino Albuquerque (PLoS ONE, 2017)
Efforts have been made to understand the processes that lead to the introduction of exotic species into local pharmacopoeias. Among those efforts, the diversification hypothesis predicts that exotic plants are introduced in local medical systems to amplify the repertoire of knowledge related to the treatment of diseases, filling blanks that were not occupied by native species. Based on such hypothesis, this study aimed to contribute to this discussion using the context of local Brazilian populations. We performed a systematic review of Brazilian studies up to 2011 involving medicinal plants, excluding those studies that presented a high risk of bias (because of sampling or plant identification problems). An analysis of similarities (ANOSIM) was conducted in different scales to test for differences in the repertoire of therapeutic indications treated using native and exotic species. We have found that although there is some overlap between native and exotic plants regarding their therapeutic indications and the body systems (BSs) that they treat, there are clear gaps present, that is, there are therapeutic indications and BSs treated that are exclusive to exotic species. This scenario enables the postulation of two alternative unfoldings of the diversification hypothesis, namely, (1) exotic species are initially introduced to fill gaps and undergo subsequent expansion of their use for medical purposes already addressed using native species and (2) exotic species are initially introduced to address problems already addressed using native species to diversify the repertoire of medicinal plants and to increase the resilience of medical systems. The reasons why exotic species may have a competitive advantage over the native ones, the implications of the introduction of exotic species for the resilience of medical systems, and the contexts in which autochthonous plants can gain strength to remain in pharmacopoeias are also discussed.